2020
DOI: 10.1016/j.compbiomed.2020.104054
|View full text |Cite
|
Sign up to set email alerts
|

Structural and molecular basis of the interaction mechanism of selected drugs towards multiple targets of SARS-CoV-2 by molecular docking and dynamic simulation studies- deciphering the scope of repurposed drugs

Abstract: The repurposing of FDA approved drugs is presently receiving attention for COVID-19 drug discovery. Previous studies revealed the binding potential of several FDA-approved drugs towards specific targets of SARS-CoV-2; however, limited studies are focused on the structural and molecular basis of interaction of these drugs towards multiple targets of SARS-CoV-2. The present study aimed to predict the binding potential of six FDA drugs towards fifteen protein targets of SARS-CoV-2 and propose the structural and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 41 publications
0
25
1
Order By: Relevance
“…The radar distribution of CQ and HCQ binding affinities towards the allelic variants of ACE2 showed superposition only in four alleles which are rs762890235 (P389H), rs755691167 (K68E), rs1299103394 (K26E), and rs778500138 (E35D) ( Figure 2 ). Recently, it has been reported that CQ and HCQ also interact differently with fifteen protein targets of SARS-CoV-2 using molecular docking and dynamics [ 39 ]. This can interfere with the inhibitory activity of ACE2, which has been previously reported [ 22 ].…”
Section: Resultsmentioning
confidence: 99%
“…The radar distribution of CQ and HCQ binding affinities towards the allelic variants of ACE2 showed superposition only in four alleles which are rs762890235 (P389H), rs755691167 (K68E), rs1299103394 (K26E), and rs778500138 (E35D) ( Figure 2 ). Recently, it has been reported that CQ and HCQ also interact differently with fifteen protein targets of SARS-CoV-2 using molecular docking and dynamics [ 39 ]. This can interfere with the inhibitory activity of ACE2, which has been previously reported [ 22 ].…”
Section: Resultsmentioning
confidence: 99%
“…These residues can play an important role in stabilizing the PLpro-ligand complexes, as previously reported. [81,83,84] In addition, the rigid docking (considering the cases with the largest negative ΔG and with a suitably good distance from the À SH of Cys111) with the other EbSe metabolites and derivatives demonstrates that the conformers of EbSe-SeGlcA, EbSeO-(S), and EbSe-OH interact predominantly with the carbonyl moiety of the amide bond of the N-phenylbenzamide group, while EbSe-GSH, EbSe-GSH-(R), and EbSe-GSH-(S) interact with the carbonyl of the peptide bond of the GSH moiety (Table S2). EbSeO-(R) and EbSeO 2 showed a Se … SH interactions, whereas EbSe-Me, EbSe-Me-OH, EbSeO-Me-(R), EbSeO-Me-(S), EbSe-Cys, Eb-SeOOH-(R), and EbSeOOH-(S) interacted with the active site of PLpro both via Se … SH and O=C … SH interactions.…”
Section: Ebse Interactions With Plpro Active Sitementioning
confidence: 99%
“…Identi cation of potential molecular targets is essential for drug repurposing [30][31][32] . Through the construction of molecular docking model between hub host gene and hub compound, it was found that folic acid (FA) and protein ILB, PTGS2, STAT1 were stable binding, and estrogen was stable binding to IL6, IL8.…”
Section: Discussionmentioning
confidence: 99%